PROFESSIONAL PRACTICE TEACHERS AND SENSE AND MEANING OF EDUCATION AND TRAINING - Robinson Jacintho de Souza; Magali Aparecida Silvestre (Editora da Universidade de Santa Cruz do Sul, 2016)
This article aim is to show the results of a research in which we tried to investigate what kind of conceptions of education and training lead the professional practice of teachers from private higher education, based on the theoretical framework of Cultural-Historical Psychology in its dialogue with the educational field. This is a qualitative research approach which has as procedure theoretical and methodological Focus Group (Gatti, 2005), conducted with teachers in private higher education institutions. For the treatment of data we made use of the Core of Significados (AGUIAR; OZELLA, 2006), which, through the narrative of the subject, helped us to identify the conceptions of education and training reflected in the discourse. As a result it was found that the meanings of education and training are more on the basis of his previous professions to teaching than in contributions developed through initial or continuing education, virtually absent processes in higher education institutions.